ANALISIS PEREKONOMIAN DAN KEMISKINAN DI INDONESIA - Megasari, Handayani; Amar, Syamsul; Idris, Idris (Program Studi Magister Ilmu Ekonomi, 2015)
This article focused on analyze (1) The effect of consumption, investment, government spending, taxes, inflation, net exports and poverty on the economy in Indonesia, (2) The effect of the economy, inflation, government spending, wages, education and unemployment on poverty in Indonesia. This research is descriptive and associative. While this type of data is the documentary data, the data source is a secondary data as well as data in the form of time series from 1983 - 2013 in this study using a simultaneous equations model analysis with Two Stages Least Squared method (TSLS). Endogenous variables in the study is the economy and poverty. While exogenous variables are consumption, investment, government spending, inflation, net exports, taxes, wages, education and unemployment. The study concluded that (1) consumption, investment, government spending, net exports significantly affect poverty in the Indonesian economy. The increase in the consumption, investment, government spending, net exports and poverty reduction will lead to an increase in the Indonesian economy. IfÂ the decline in the consumption, investment, government spending, net exports and an increase in poverty will lead to a decrease in the Indonesian economy. While inflation and taxes are not a significant effect on the economy in Indonesia (2) The economy, government spending and unemployment significantly influence poverty in Indonesia. If the economy and government spending has increased and unemployment decreased, the poverty in Indonesia will decline. However, if the economy and government spending has decreased and unemployment has increased the poverty in Indonesia will increase. Meanwhile, inflation, wages and education had no significant effect on poverty in Indonesia. Keywords : Consumption, Investment, Government Spending, Taxes, Inflation, Net Export, Wages,Â Education, Unemployment, Economy and Poverty